GEN XERS IN UNCERTAIN TIME OF WORKING REMOTELY – AN EMPLOYEE’S PERSPECTIVE - Żarczyńska-Dobiesz, Agnieszka; Janiak-Rejno, Iwona; Chomątowska, Barbara Chomątowska (Organizacja i Kierowanie, 2023)
The main goal of the paper is to explore the opinions of Generation X employees on remote work during the SARS-CoV-2 pandemic. A quantitative research method was used, specifically a diagnostic survey using the surveying technique and CAWI methods. The original questionnaire was based on two measurement scales: ordinal (Likert scale) and nominal (binary and categorical). The survey ended with a metric that enabled the collection of the socio-demographic characteristics of the studied population. Subsequently, a two-way data analysis method was applied as part of the adopted research methodology. Due to the nominal nature of the variables, frequency and percentage statistics were used in the statistical evaluation. For variables on the Likert scale, measures of descriptive statistics were used. Correctly completed questionnaires by 241 respondents were qualified for the final analysis. Research shows that the pandemic reality has created new challenges, forcing significant changes in personnel management practices. The obtained results made it possible to conclude that Gen X workers were highly involved in their workplace while working remotely. Unfortunately, they were also overworked and tired. Gen Xers strive to effectively perform their duties, regardless of whether they work at the company’s headquarters or at home. Due to the limitations of the research sample, it is essential to underline that generalizing the research results must be done with caution. Originality/value – Our paper contributes to the latest insight into remote work from the perspective of Gen Xers during the pandemic. The authors of this article recognize that it would be worthwhile to conduct the study over a longer period, which would allow for identifying the level of adaptation to remote work.